Development of an e-module for eco-enzyme production in biotechnology learning using the SETS approach oriented toward problem-solving skills - Nila Permatasari; Sajidan Sajidan; Umi Fatmawati (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Theoretical and less contextual biotechnology learning often hinders students' problem-solving skills. This research aims to develop and test the feasibility and practicality of an eco-enzyme production e-module with a SETS (Science, Environment, Technology, and Society) approach oriented toward problem-solving skills. Development followed the ADDIE model, but evaluation was limited to expert validation and practicality testing, without conducting a full experimental effectiveness test. The participants consisted of 3 science teachers and 64 ninth-grade students from a public junior high school in Baki District, Sukoharjo. Data were collected using a needs analysis questionnaire, expert validation sheets (for materials and media), user response questionnaires, and problem-solving skills instruments adapted from Polya and Santrock. Quantitative data were analyzed descriptively to determine the feasibility and practicality percentages. Validity testing was conducted using item-total correlation, and reliability was assessed using Cronbach's alpha. Qualitative input from experts and users was analyzed descriptively for product improvement. The results show that the e-module is highly feasible, with scores of 91.1% from content experts and 86.9% from media experts. The practicality test was also very high, with 94.5% from teachers and 86.9% from students. These findings suggest that the e-module is both valid and practical, and is designed to enhance problem-solving skills in biotechnology learning.Abstrak. Pembelajaran bioteknologi yang bersifat teoretis dan kurang kontekstual seringkali membatasi keterampilan pemecahan masalah siswa. Penelitian ini bertujuan untuk mengembangkan serta mengevaluasi kelayakan dan kepraktisan e-modul produksi eco-enzyme dengan menggunakan pendekatan SETS (Science, Environment, Technology, and Society) yang berorientasi pada keterampilan pemecahan masalah. Pengembangan mengikuti model ADDIE dengan evaluasi yang difokuskan pada validasi ahli dan uji kepraktisan, tanpa melakukan uji efektivitas eksperimen secara penuh. Partisipan penelitian terdiri atas 3 guru IPA dan 64 siswa kelas IX dari salah satu SMP negeri di Kecamatan Baki, Sukoharjo. Pengumpulan data menggunakan angket analisis kebutuhan, lembar validasi ahli materi dan media, angket respons pengguna, serta instrumen keterampilan pemecahan masalah yang diadaptasi dari Polya dan Santrock. Data kuantitatif dianalisis secara deskriptif untuk menentukan skor kelayakan dan kepraktisan, dengan validitas diuji menggunakan korelasi item–total dan reliabilitas menggunakan Cronbach’s alpha. Umpan balik kualitatif dari ahli dan pengguna dianalisis secara deskriptif untuk perbaikan produk. Hasil penelitian menunjukkan bahwa e-modul sangat layak, dengan skor 91,1% dari ahli materi dan 86,9% dari ahli media. Uji kepraktisan juga menunjukkan hasil sangat tinggi, yaitu 94,5% dari guru dan 86,9% dari siswa. Temuan ini menegaskan bahwa e-modul valid dan praktis, serta berpotensi meningkatkan keterampilan pemecahan masalah siswa dalam pembelajaran bioteknologi.